Fabricação e estudo de um fogão solar multifocal para cocção de alimentos - Medeiros Júnior, Aldo Paulino de (2016)
The use of composite materials has been the subject of numerous scientific papers in Brazil and worldwide. Solar energy is the primary energy source and the option is more environmentally sustainable and more social of all energy sources. It is manufactured and studied the capabilities and baking feasibility of a solar cooker will multifocal concentration with reflective parabolas made of composite material for the cooking food for residential, urban and rural purposes. It consisted of four parabolas made of composite materials, formed by orthophthalic resin added to the elements: curtain fabric, knitted fabric, cotton bag, burlap sack (jute). The main feature of the proposed solar stove was cooking capacity of four foods simultaneously, which gave him a technological novelty character in cooking. The manufacturing and assembly processes will be presented. The solar cook structure has mobility apparent movement of the sun. It is an environmentally friendly, clean, renewable option since it is an alternative to the large-scale use of firewood for cooking food, and a great help to the disadvantaged populations that do not stop growing. Thermal and economic feasibility of solar cooker proposed for obtaining cooking and baking food have been demonstrated. To demonstrate the feasibility of using solar cooker proposed were cooked various foods of Northeastern typical food. It has proven its ability to produce the cooking of food in a typical meal, rice, beans, pasta and meat in just one hour.